KEANEKARAGAMAN LAMUN DAN MAKROZOOBENTOS SEBAGAI INDIKATOR KONDISI PERAIRAN PANTAI SINDHU, SANUR, BALI - I Made Sara Wijana; Ni Made Ernawati; Made Ayu Pratiwi (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2019)
Sindhu Beach is part of the Sanur beach area. Sanur area is one of 11 strategic national tourism areas in Bali. Beach tourism activities have the potential to cause degradation of coastal ecosystems. Ecosystem changes can be determined using bioindicators. This study aims to determine the condition of the Sindhu Coast waters ecosystem based on seagrass diversity and macrozoobenthos as indicators. This research was conducted in November 2019 at Sindhu Beach. Seagrass observations and macrozoobenthos sampling were carried out at four stations with three replications at each station. Data and samples were collected using the quadratic transect method. Eight species of seagrass were found in Sindhu Beach with a percentage of cover between 16.33% - 63.37% and density between 1572 ind / m2 - 3314.4 ind / m2. The average value of the seagrass diversity index was 1.24, the average uniformity index was 0.78, and the average dominance index was 0.32. Types of macrozoobenthos found were 23 species with abundances ranging from 2.33 ind / m2 - 28.33 ind / m2. The average value of macrozoobenthos uniformity index is 1.50, the average diversity index is 0.68 and the average dominance index is 0.36. Based on the index value shows that the waters of Sindhu Beach are in good condition or there is no ecologically significant pressure.